Investigating the Role of ChatGPT as an AI-Powered Writing Assistant in Enhancing Essay Cohesion and Coherence The Case of Third Year Students of English at the University of Souk-Ahras - FAREK Riadh (My University, 2026)
Abstract This study investigates the impact of ChatGPT on improving coherence and cohesion in EFL students’ essay writing. The research was conducted with third-year English students, aiming to examine whether the use of ChatGPT can enhance students’ writing performance and to explore their perceptions of this tool. A mixed-method approach was adopted, combining both quantitative and qualitative data. A pre-test and post-test were used to measure students’ writing performance before and after using ChatGPT, while a questionnaire was administered to collect students’ perceptions regarding its use in essay writing. The results revealed a clear improvement in students’ writing performance, particularly in terms of organization, coherence, and cohesion. The comparison between pre-test and post-test showed that students were able to produce more structured and logically connected essays after using ChatGPT. In addition, the questionnaire findings indicated that most students use ChatGPT as a supportive tool for generating ideas, organizing their essays, and improving language accuracy. Students generally expressed positive attitudes toward its use, although some concerns were raised about overreliance and its potential impact on critical thinking. The study concludes that ChatGPT can be an effective tool for improving EFL students’ essay writing, especially in terms of coherence and cohesion; however, its use should be guided to ensure that students maintain their independent writing skills. ----------------- الملخص تهدف هذه الدراسة إلى استكشاف تأثير استخدام ChatGPT في تحسين التماسك والانسجام في كتابة المقالات لدى طلبة اللغة الإنجليزية كلغة أجنبية. أُجريت الدراسة على طلبة السنة الثالثة تخصص اللغة الإنجليزية، بهدف معرفة ما إذا كان استخدام ChatGPT يمكن أن يساهم في تحسين أداء الطلبة في الكتابة، وكذلك استكشاف تصوراتهم حول هذا الأداة. تم اعتماد منهج مختلط يجمع بين البيانات الكمية والنوعية. حيث تم استخدام اختبار قبلي واختبار بعدي لقياس أداء الطلبة قبل وبعد استخدام ChatGPT، بالإضافة إلى استبيان لجمع آراء الطلبة حول استخدامه في كتابة المقالات. أظهرت النتائج تحسناً واضحاً في أداء الطلبة، خاصة من حيث تنظيم الأفكار، والتماسك، والانسجام. كما أظهرت المقارنة بين الاختبار القبلي والبعدي أن الطلبة أصبحوا قادرين على كتابة مقالات أكثر تنظيماً وترابطاً بعد استخدام ChatGPT. إضافة إلى ذلك، بينت نتائج الاستبيان أن معظم الطلبة يستخدمون ChatGPT كأداة مساعدة لتوليد الأفكار، وتنظيم المقالات، وتحسين دقة اللغة. كما عبّر الطلبة عن مواقف إيجابية تجاه استخدامه، رغم وجود بعض المخاوف المتعلقة بالاعتماد المفرط عليه وتأثيره على التفكير النقدي. وتخلص الدراسة إلى أن ChatGPT يمكن أن يكون أداة فعالة في تحسين كتابة المقالات لدى طلبة اللغة الإنجليزية كلغة أجنبية، خاصة فيما يتعلق بالتماسك والانسجام، إلا أن استخدامه يجب أن يكون موجهاً ومتوازناً لضمان تطوير مهارات الكتابة المستقلة لدى الطلبة. ----------------------------- Résumé Cette étude vise à examiner l’impact de l’utilisation de ChatGPT sur l’amélioration de la cohérence et de la cohésion dans la rédaction des essais chez les apprenants de l’anglais langue étrangère (EFL). La recherche a été menée auprès des étudiants de troisième année d’anglais, dans le but de déterminer si l’utilisation de ChatGPT peut améliorer leurs performances en écriture, ainsi que d’explorer leurs perceptions de cet outil. Une approche mixte a été adoptée, combinant des données quantitatives et qualitatives. Un pré-test et un post-test ont été utilisés pour mesurer les performances des étudiants avant et après l’utilisation de ChatGPT, tandis qu’un questionnaire a été administré pour recueillir leurs perceptions concernant son utilisation dans la rédaction des essais. Les résultats ont montré une amélioration claire des performances des étudiants, notamment en termes d’organisation, de cohérence et de cohésion. La comparaison entre le pré-test et le post-test a révélé que les étudiants étaient capables de produire des essais plus structurés et logiquement organisés après l’utilisation de ChatGPT. De plus, les résultats du questionnaire ont indiqué que la majorité des étudiants utilisent ChatGPT comme un outil de soutien pour générer des idées, organiser leurs essais et améliorer la précision linguistique. Les étudiants ont généralement exprimé des attitudes positives envers son utilisation, bien que certaines préoccupations aient été soulevées concernant une dépendance excessive et son impact potentiel sur la pensée critique. L’étude conclut que ChatGPT peut être un outil efficace pour améliorer la rédaction des essais chez les apprenants EFL, en particulier en ce qui concerne la cohérence et la cohésion ; toutefois, son utilisation doit être encadrée afin de garantir le développement des compétences rédactionnelles autonomes.
Keywords: ChatGPT; EFL writing; coherence; cohesion; essay writing; artificial intelligence; ChatGPT، الكتابة باللغة الإنجليزية كلغة أجنبية، التماسك، الانسجام، كتابة المقال، الذكاء الاصطناع; écriture en EFL; cohérence; cohésion; rédaction d’essais; intelligence artificiell.